A linear programming approach for finding efficient allocation of resource In Jilin, China - Qin, Yuchen (Kansas State University, 2018)
China has always been one of the world’s largest grain producers, and Jilin is the largest grain-producing province in China. According to the Report on the Work of the Government 2018, the yield per mu (0.165 acre) has remained the first of the country for the past five years; and the grain commodity rate, the volume of transfers and the possession per capita have remained at the forefront of the country, making a significant contribution to ensuring national food security. This study is to compare efficient allocation of resources through designing a linear programming model with current allocation of resources to find out potential improvements and policy suggestions for future agricultural structure, rational cultivation of grains and market prediction for Jilin, China. In addition, this study examines what role the government regulations play in the grain production in China and how the trade war affects the grain production.
Keywords: Optimization; Linear Programming; Government Regulations; Trade War